STYLISTICS AND LEVELS OF LANGUAGE. PHONO-GRAPHICAL AND MORPHOLOGICAL LEVEL IN STYLISTIC ANALYSIS - Akhnazarov Abdulazizbek Boyxo’roz o’g’li; Zilola Abdurakhmanova Yoqubjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: Stylistics is a fascinating branch of linguistics that delves into the intricate nuances of language usage, aiming to unravel the artistry embedded in words. Two significant levels of language, the phono-graphical and morphological, form the bedrock of stylistic analysis, providing a lens through which we can examine how sounds and structures contribute to the aesthetic and communicative aspects of a text.